Kearifan Lokal Masyarakat Dieng dalam melestarikan Harmoni dan Budaya Ruwatan Rambut Gimbal - Rifqi Fathulhuda; Nur Aini Zakiyatin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
This research examines the local wisdom of the Dieng Highlands community through the Ruwatan Rambut Gimbal tradition as an effort to maintain harmony between humans, nature, and the spiritual dimension. The phenomenon of dreadlocks is considered a "mandate" that carries implications for children's well-being, thus requiring a purification ritual to free them from misfortune (sukerta). This study aims to analyze the strategies for preserving these cultural values amidst modernization. Using a descriptive qualitative method, data were collected through observation, in-depth interviews with traditional leaders, and documentation studies. The results indicate that the existence of this tradition is maintained through synergistic collaboration between the community, local government, and cultural communities via the Dieng Culture Festival (DCF). This tradition functions not only as a sacred ritual and social identity binder but also provides a positive economic impact on local welfare through cultural tourism. In conclusion, Dieng's local wisdom is dynamic and adaptive; it successfully integrates traditional values into modern platforms without losing its sacred essence, ensuring the sustainability of cultural heritage for future generations.